Sustained immunologic and virologic efficacy after four years of highly active antiretroviral therapy in human immunodeficiency virus infected children in Thailand - Thanyawee Puthanakit (2018)
We report the long-term efficacy of highly active antiretroviral therapy (HAART) in 107 antiretroviral-naive human immunodeficiency virus (HIV)-infected Thai children. In an intention-to-treat analysis, 70% of the children had undetectable HIV RNA titers after 192 weeks of HAART. The mean CD4 cell percentage increased from 5.3% to 26.6%. HAART is effective for HIV-infected children in this resource-poor setting despite initiation of treatment in the advanced stage of disease. © 2007 Lippincott Williams & Wilkins, Inc.